Veni, Vidi, Vici: Immigrant Entrepreneurship at the Historical Town of Melaka and Venice - Ramli, Nur Suhaili (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2020)
This aim of this study is to investigate the strategy and influence factors of immigrant entrepreneurship at the World Heritage Site of Melaka and Venice. It focused only the immigrant entrepreneurs that involved directly in the tourism industry within both cities. A theory-building qualitative approach was followed. It gathered the data by conducting twelves semi-structured interviews in the historical site of Venice and Melaka. It adopted thematic analysis to analyse the transcript interviews data that stored in NVivo. Both cases were presented in a comparative view. The original contributions indicated that immigrant entrepreneurs: (1) applied market segmentation and niche products, (2) played in pricing strategy, and (3) promoted their businesses using their strong immigrant-network ties at the host country. Also, there are some similarities and differences in their approach compared to the local entrepreneurs were generally discussed. This paper contributes to understanding better the immigrant entrepreneurship phenomenon in both Venice and Melaka. Also, several limitations and recommendations for further study were discussed.